1999
DOI: 10.1002/nha3.10099
|View full text |Cite
|
Sign up to set email alerts
|

Can We Really Teach Test‐Taking Skills?

Abstract: A group of adult learners enrolled in a teacher training program were not able to attain the state mandated scores on the Scholastic Aptitude Test (minimum scores on the math and language sections of the test were required for certification). Coaching and relaxation skills were introduced to alleviate test anxiety, increase the cognitive thinking processes, and provide support needed to achieve success in the testing environment. Coaching and relaxation skills proved to be effective in helping individuals achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Consequently, context-based questions that reflect the real world may be used to reduce the test anxiety of students and improve their attitudes towards science. Previous studies (Erbe, 2007;Berk & Nanda, 2006;Noh et al, 2000;Stober, 2004;Foster, Paulk, & Dastoor, 1999;Kondo, 1996;Serok, 1991) have reported that various measures and strategies reduced test anxiety among students. Whereas, it has not been proved from the literature that context-based questions can reduce students' test anxiety and improve their attitudes towards science, this research has shown that context-based questions can reduce test anxiety and improve attitudes towards science.…”
Section: Discussionmentioning
confidence: 94%
“…Consequently, context-based questions that reflect the real world may be used to reduce the test anxiety of students and improve their attitudes towards science. Previous studies (Erbe, 2007;Berk & Nanda, 2006;Noh et al, 2000;Stober, 2004;Foster, Paulk, & Dastoor, 1999;Kondo, 1996;Serok, 1991) have reported that various measures and strategies reduced test anxiety among students. Whereas, it has not been proved from the literature that context-based questions can reduce students' test anxiety and improve their attitudes towards science, this research has shown that context-based questions can reduce test anxiety and improve attitudes towards science.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, Ahmed and Pollitt (2000) observed that context-based questions were favorable for high-performing students and also recognized the contribution of context-based questions in reducing students' test anxiety. The results of previous studies (Berk & Nanda, 2006;Erbe, 2007;Foster, Paulk, & Dastoor, 1999;Kondo, 1996;Noh et al, 2000;Serok, 1991;Stöber, 2004) indicate that various measures and strategies reduce test anxiety among students. However, these studies have not substantiated that context-based questions can reduce students' test anxiety and improve their science achievement.…”
Section: Discussionmentioning
confidence: 95%
“…Curriculum developers first reviewed the limited (though helpful) professional literature on the topic of technical exam preparation (Bureau of Vocational, Technical, and Adult Education 1992; Collins 1999; Foster, Paulk, and Riederer Dastoor 1999; Mercer County Community College 1992) and curricula from other test-preparation programs (e.g., for utility workers and for the General Aptitude Test Battery) to identify potential test-preparation strategies to adapt for this program. Developers then clarified which exams to focus on first, based on the MTA’s announcements of the exams to be held in the coming months.…”
Section: A Case Study Of a Major Education Initiative For Public Tranmentioning
confidence: 99%